Long term yield response of low frequency tapping and yield stimulation in clone RRII 105 - Karunaichamy, K.; Thomas, K.U.; Rajagopal, R. (Journal of Plantation Crops, 2013)
An experiment was laid out in the Experimental Farm Unit of Rubber Research Institute of India located at Kottayam, Kerala (9º32’N; 76º36’E) to compare the long term (fifteen years) yield response of clone RRII 105 to low frequency tapping with varying levels of yield stimulation. Reduction in cost of production by adopting low frequency tapping with stimulation (ethephon) is one of the approach to make rubber cost effective. Cumulative dry rubber yield over fifteen years under d3, d4 and d6 frequencies with stimulation is comparable to unstimulated alternate daily tapping (d2). There was no reduction in yield in the renewed bark (BI-1) compared to virgin panel (BO-1) and high yield was obtained in BO-2 panel under d3 and d4 frequencies of tapping. Total tapping days during the study period for d2, d3, d4 and d6 frequencies of tapping days were 2161, 1470, 1105 and 766 days, respectively. Thus, by adopting d3, d4 and d6 frequencies of tapping, requirement of tapper was reduced by 32, 49 and 65 per cent respectively, compared to alternate daily tapping. Benefits of adopting LFT are long term sustainable yield and extended period of tapping on the same panel leading to longer economic life of the trees. Adoption of LFT is also expected to reduce the impact of the scarcity of skilled tappers in rubber plantation sector.